MORPHOLOGICAL AND BIOLOGICAL TRAITS OF LARGE-FRUITED CHERRY PLUM (PRUNUS x ROSSICA EREMIN) AND THEIR IMPORTANCE FOR EXPERT EXAMINATION OF VARIETIES FOR THEIR DISTINCTNESS, HOMOGENEITY AND STABILITY (DHS) - U. I. Kantsayeva; V. M. Gorina (Труды по прикладной ботанике, генетике и селекции)
This work presents the results of long-term research on morphological and biological traits of six hybrid cherry plum varieties (Prunus х rossica Eremin). Such morpho-biological traits are shown to have significance during expert examination of varieties for distinctness, homogeneity and stability. The studied varieties (‘Andromeda’, ‘Desertnaya Rannyaya’, ‘Obil'naya’, ‘Olen'ka’, ‘Rumyanaya Zor'ka’ and ‘Femida’) meet the criteria of distinctness, homogeneity and stability, which has been confirmed by the experts from the State Variety Testing Commission.